Germination of Quercus ilex and Q. pubescens in a Q. ilex coppice - Bran, D; Lobreaux, O; Maistre, M; Perret, P; Romane, F (Plant Ecology, 1990)
Quercus ilex L. (holm oak) coppices, widespread around the Mediterranean basin, are probably the result of 5 000 years of prolonged human disturbance of the original Quercus pubescens Willd. (downy oak) forests. Since disturbance has almost ceased in recent years, a question arises as to the development of these coppices: will the Q. pubescens forests return, or will Q. ilex remain the dominant species? To investigate the phenomenon, we analyzed the first stages, i.e. germination of the two species in holm oak coppices. Our experiments show that both species germinated better in coppices than in clearings or clear-cuts. Moreover, Q. pubescens appears to be slightly favored above Q. ilex and it is suggested auto-allelopathy is involved, at least partially inhibiting the germination of Q. ilex.
Keywords: dynamics; Mediterranean climate; Southern France; succession

Local characterization of vegetation through growth forms: Mediterranean Quercus ilex coppice as an example - Floret, C; Galan, N J; Floc'h, E; Orshan, G; Romane, F (Plant Ecology, 1987)
Growth forms are considered from two viewpoints: a descriptive and a functional one. Mono-character growth forms and their biological spectra were used to test whether they can characterize certain underlying processes in Quercus ilex coppice in southern France. Correspondence analysis of 35 mono-character growth forms of 203 described taxa shows that location of renewal buds is a good integrating indicator of plant adaptations to the environment. Two of these characters (renewal bud location, Le. Raunkiaer's main life forms, and leaf consistency) appear to vary significantly along a gradient of increasing environmental constraints, especially climatic ones.
Keywords: coppice; growth form; Life form; Mediterranean climate; Quercus ilex L; Southern France